Formation of the iron-sulfur cluster of ferredoxin in isolated chloroplasts - Takahashi, Yasuhiro (1986)
The formation of the iron-sulfur cluster of ferredoxin was examined in vitro by incubating isolated chloroplasts with [(35)S]cysteine. The ferredoxin molecule was radioactively labeled in chloroplasts without synthesis of its polypeptide and comigrated with holoferredoxin during polyacrylamide gel electrophoresis under nondenaturing conditions. When the labeled ferredoxin was denatured by the addition of trichloroacetic acid, radioactive acid-labile sulfide in the cluster was released from the polypeptide as a gas and trapped in a 0.1 M NaOH solution. These results indicate that the sulfur atom derived from cysteine was incorporated into ferredoxin through formation of the iron-sulfur cluster. This process was stimulated by light and inhibited by the electron transport inhibitor, dichlorophenyldimethylurea, and the uncouplers, atebrin and gramicidin, but not by the protein synthesis inhibitor, chloramphenicol. These inhibitory effects were reversed by the addition of ATP to the incubation mixture. Formation of the iron-sulfur cluster of ferredoxin in chloroplasts is thus dependent on ATP.